"Energy Relay Center" for doped mechanoluminescence materials: a case study on Cu-doped and Mn-doped CaZnOS. Issue 2 (12th December 2016) - Huang, Bolong; Peng, Dengfeng; Pan, Caofeng
Abstract : Schematic for reversible and irreversible mechanical quenching, as well as enhanced luminescence from mechanical loading. Abstract : We unraveled the mechanisms of transition metal-doped mechanoluminescent materials through a case study of CaZnOS. We found that the native point defect levels in Cu or Mn-doped CaZnOS system acted as energy relay centers for luminescence energy transfer. In combination with native point defect levels, discussed in a previous study [ Phys. Chem. Chem. Phys., 2016, 18, 25946], we found that phosphor luminescence belongs to two different mechanisms. For Cu-doping, it occurs by the path via the conduction band minimum to the Cu-t2g level of the 3d orbital localized in the band gap. The hole-drifting effect was found to support the reported red-shifting of the emission. Both reversible and irreversible mechanical quenching were attributed to the spatially separated electrons recombining with the hole localized on the Cu-t2g level within the gap at levels below or above respectively. For Mn-doping, this occurs by a collaborative luminescence assisted by native point defects, and the excited states of Mn 2+ overlap with the conduction band edge. The coexistence of MnZn and MnCa was confirmed, but was relatively low in MnCa . The concentration quenching effect, as well as the red-shift of absorption, shows a strong correlation with native point defect levels and the relative position of the 4T1 ( 4 G) state for both MnZn and MnCa . Further simplified approximations were used for modeling such concentration quenching effects.